News from AG Draconis - Leedjärv L. (Open Astronomy, 2012)
AG Dra is a classical symbiotic star that undergoes major outbursts at intervals between 12-15 years. We present spectroscopic observations of four emission lines (Hα, Hβ, He II 4686 Å, Raman scattered OVI 6825 Å) before, during and after the major outburst that started in 2006. Interesting strengthenings of the emission lines took place in late 2005 and in early 2008. the latter was followed by a very deep minimum in the line strengths in 2008–2009.